2021
DOI: 10.1071/sh20208
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of providing HIV pre-exposure prophylaxis across Australian clinics: qualitative insights of clinicians

Abstract: Background: HIV pre-exposure prophylaxis (PrEP) has been rapidly implemented in Australia, initially through restricted access in demonstration studies, and then through prescribing across sexual health clinics and general practice settings. In 2018, PrEP was publicly subsidised for people with Medicare (universal health insurance for citizens, permanent residents and those from countries with reciprocal arrangements). There is little research examining the experiences of PrEP providers in Australia, and exist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 45 publications
2
24
0
Order By: Relevance
“…We found that participants who anticipated not being confronted regularly with a demand for PrEP, perceived the investment of having to re-familiarize with PrEP on limited occasions too much of a burden. This barrier of a lack of demand experienced by some FPs was also reported in a study among PrEP-prescribing FPs in Australia ( 33 ). Alternatively, we found that some FPs expressed a particular interest in being able to initiate clients on PrEP without the need for referral.…”
Section: Discussionsupporting
confidence: 59%
“…We found that participants who anticipated not being confronted regularly with a demand for PrEP, perceived the investment of having to re-familiarize with PrEP on limited occasions too much of a burden. This barrier of a lack of demand experienced by some FPs was also reported in a study among PrEP-prescribing FPs in Australia ( 33 ). Alternatively, we found that some FPs expressed a particular interest in being able to initiate clients on PrEP without the need for referral.…”
Section: Discussionsupporting
confidence: 59%
“…However, there were still reservations among some Australian clinicians to promote ED-PrEP because of beliefs that the regimen is confusing, less effective, or more difficult to use than daily PrEP, and that it is not a priority compared with discussing condoms, daily PrEP, and HIV testing. 42,43 Furthermore, although the Australian PrEP clinical guidelines endorsed ED-PrEP in 2019, daily PrEP is the only regimen approved by the Australian Therapeutic Goods Administration. 44 Regardless, even among those aware of the regimen, knowledge about how to take ED-PrEP was still low.…”
Section: Discussionmentioning
confidence: 99%
“…‘Sexual health nurse’ included registered nurse, clinical nurse consultant, clinical nurse specialist, and nurse practitioner. While most nurses (except nurse practitioners) cannot prescribe PrEP in Australia, we included nurses in our study as some were permitted to dispense PrEP during trials, and many continued to educate and assess patients for PrEP alongside prescribing clinicians (see Smith, Haire, et al., 2021). To ensure confidentiality when quoting participants, only their profession is reported, that is, [P01 – Sexual Health Nurse].…”
Section: Methodsmentioning
confidence: 99%
“…In Australia, PrEP was initially introduced in 2015, and made publicly available in 2018, available via prescription from a doctor or nurse practitioner (Smith, Haire, et al., 2021). Rapid scale‐up of PrEP in New South Wales, Australia demonstrated that PrEP can be successful in preventing HIV transmissions (Grulich et al., 2021).…”
Section: Introductionmentioning
confidence: 99%